(untitled) (Prosiding Konseling Kearifan Nusantara (KKN), 2025)
Assertive behavior is a behavior that every individual needs to have, especially for generation z which causes individuals to interact directly and communicate virtually. Assertive behavior includes how individuals are able to express their opinions and thoughts. There are several factors that influence individual assertive behavior including: gender, parenting patterns, age, education level, and economic conditions. so this study aims to conceptually determine how to improve the assertive behavior of generation Z. This study is expected to provide an understanding of the assertive behavior of generation Z, as well as provide insight for educators to pay special attention to students’ assertive behavior to optimize the learning process and prepare students to enter a wider scope.